2018
DOI: 10.1515/jpm-2017-0394
|View full text |Cite
|
Sign up to set email alerts
|

Does ultrasound-guided intervention during repeat cesarean sections improve uterine scar architecture and reduce the number of scars? A prospective controlled clinical intervention trial

Abstract: Purpose To evaluate whether intraoperative ultrasound-guided detection and resection of the uterine scar during repeat/second cesarean can reduce the number of scars and improve uterine scar architecture. Materials and methods A prospective controlled clinical intervention trial was performed with the following groups: control group 1 (CS1-G): first cesarean; control group 2 (CS2-G): second cesarean utilizing the usual procedure and intervention group (Int-G): repeat/second cesarean with intervention. Transvag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…The myometrial thinning at the scar was measured as a deficiency ratio and a ratio above 50% was considered to be severe. Our proposed RMT ratio has an inverse relationship to such a deficiency ratio and a higher RMT ratio reflects better healing [13]. Our data show both median and average RMT ratios of around 56% which contradicts the assumption that a deficiency above 50% is severe.…”
Section: Discussioncontrasting
confidence: 80%
“…The myometrial thinning at the scar was measured as a deficiency ratio and a ratio above 50% was considered to be severe. Our proposed RMT ratio has an inverse relationship to such a deficiency ratio and a higher RMT ratio reflects better healing [13]. Our data show both median and average RMT ratios of around 56% which contradicts the assumption that a deficiency above 50% is severe.…”
Section: Discussioncontrasting
confidence: 80%
“…The changes of the uterine anatomy caused by a CS can be responsible for complications in a subsequent pregnancy, and the ultrasound findings of these changes are believed to be helpful in assessing the probability of obstetrical complications [ 16 , 17 ]. Most studies were conducted before the methodology for measuring post-cesarean uterine niches was established and standardized by Jordans et al guidelines [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seliger et al measured a deficiency ratio of the niche depth in relation to the combination of RMT and niche depth. Thinning at the scar location with a deficiency ratio greater than 50% was classified as severe deficiency [ 17 ]. Our results indicate that such a deficiency is not severe considering that it is very close to our median.…”
Section: Discussionmentioning
confidence: 99%
“…A ratio of more than 50% was classified as severe deficiency. 17 Previous work measured the CS scars longitudinally during the pregnancy and showed that the measurements are reproducible, but they utilized transvaginal ultrasound throughout second and third trimesters. 8 Transabdominal ultrasound is more practical in the later stages of pregnancy; thus it should be the preferred method for evaluating the lower uterine segment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies similarly utilized ratios for calculating the degree of thinning at the scar level. A ratio of more than 50% was classified as severe deficiency 17 …”
Section: Discussionmentioning
confidence: 99%